An Analysis of Reflective Thinking and Literacy Competencies in Inquiry Learning Model Applications - Islami, Aica Wira; Mulyono, Mulyono; Fauzi, Kms. Muhammad Amin (Jurnal Perspektif, 2025)
The study aims to describe students' answers in solving reflective thinking problems and literacy of the Pythagorean theorem material, reducing student errors in completing reflective thinking tests and mathematical literacy skills through the application of the inquiry learning model. This study uses a qualitative approach. The subjects in this study were 30 students of class VIII-1 MTs Abata Al Washliyah in the 2024/2025 academic year. The results of the study are as follows: students' answers in reflective thinking and literacy on the Pythagorean theorem material on the reacting, elaborating and contemplating indicators and on students' literacy skills in solving problems on the indicators of being able to describe problems systematically; being able to use concepts, facts, procedures, and reasoning in mathematics; and interpreting mathematics to solve problems. Errors in thinking and reflective literacy skills in the application of the inquiry learning model, students with high categories did not experience errors, in the medium category, students experienced transformation errors, process skill errors, low categories, students experienced errors in understanding questions; transformation errors and process skill errors.